Imagining paganism through the ages : studies on the use of the labels "pagan" and "paganism" in controversies - Müller, Daniela; Verheyden, Joseph, 1957- (Bibliotheca Ephemeridum theologicarum Lovaniensium, 2020)
This volume contains the proceedings of the first International Colloquium of the Research Centre "Polemikos" that was founded in 2016 by Joseph Verheyden (KU Leuven) and Daniela Müller (RU Nijmegen). The Centre is dedicated to the study of the history of religious polemics. This first meeting, held 14-16 of March 2018 in Leuven, studied a commonly known and broadly used way to discredit an adversary by using labels, in particular the negative label par excellence - that of being "a pagan". For practical reasons, the focus was limited to voices and evidence of Western origin - from the famous adversus Paganos literature to the controversies on native populations after the discovery of the New World and the place and role to be given to more "rationalistic" approaches to the Christian faith in the (early) modern period. The case studies presented here illustrate that the label can receive many different meanings. Among these are the characterisation of the others as strangers or barbarians and the accusation of committing idolatry, but also all sorts of insinuations or claims of immoral behaviour and more outlandish ones that associate these "pagan" others with demonic schemes. The last two contributions have less to do with "fighting" and more with "imagining" paganism, though these two aspects overlap as is shown in several of the essays; hence the choice for "Imagining Paganism" in the general title.